Effect Special Exercises of weight training to Develop the Strength Endurance and the Performance of some individual Offensive Skills in Basketball - mahmmed, omer (Journal of Physical Education, 2010)
Chapter one The aim of the study To identify the effect of special exercise of ballasting in the development of the strengths endurance for individuals the research sample.To identify the effect of strengths endurance on performance of some compound offensive skills in basketball for individuals the research sample.The hypothesis of the study There are significant statistical differences in the development of strength endurance for individuals the research sample and under between pre and post tests and in favors of the post test.There are significant statistical differences in the performance of some compound offensive skills in basketball for individuals the research sample between pre and post tests and in favors of the post test. Chapter two The Researcher deals with in this chapter some theoretical topics on the subject of his research, as touched on methods and manners strength endurance and training.Chapter three This chapter contains the procedures of the study , the researcher adopted experimental method on a sample of (12) players from the youth club .Chapter four This chapter present the results were displayed, analyzed and discussed through the use of a number of statistical methods,Chapter five The Conclusions There are significant statistical differences between the results of pre and post tests in physical tests on the special physical exercise of ballasting, which indicates that effect and influence to development the strength endurance on the players of the experimental group. The Recommendations In the light of the results the researcher recommended the following The necessity of paying attention by the trainers using ballasting in their training throughout the year through the allocation of days an independent ballasting training .